Confirmation of canine acanthomatous ameloblastoma using RAS Q61R immunohistochemical staining of formalin-fixed paraffin-embedded tissues - Peralta, Santiago; Marcinczyk, Magdalena M.; Katt, William P.; Duhamel, Gerald E. (Frontiers in Veterinary Science, 2023)
Differentiating canine acanthomatous ameloblastoma (CAA) from oral squamous cell carcinoma (OSCC) based on routine histopathology can be challenging. We have previously shown that more than 95% of CAAs harbor an HRAS p.Q61R somatic mutation, while OSCCs carry either wild-type alleles or other MAPK pathway activating mutations (e.g., HRAS p.Q61L, BRAF p.V595E). Given that HRAS p.Q61R mutations are highly prevalent in CAA, we hypothesized that a RAS Q61Rspecific rabbit monoclonal antibody may be a useful tool for confirmation of CAA by immunohistochemical (IHC) staining. In the present study, we assessed IHC staining of archived formalin-fixed and paraffin-embedded biopsy samples with a diagnosis of CAA (n=23), using a RAS Q61R-specific rabbit monoclonal antibody (SP174) and an automated IHC stainer. Negative control samples consisted of HRAS p.Q61R mutation-negative OSCC tumors with either a known HRAS p.Q61L mutation (n=1), BRAF p.V595E mutation (n=4), or wild-type corresponding alleles (n=3). We found that all 23 CAAs showed diffuse and strong membranous RAS Q61R immunoreactivity (100% sensitivity), while none of the 8 OSCCs showed immunoreactivity (100% specificity). The data supports the use of RAS Q61R-specific rabbit monoclonal antibody for diagnostic IHC confirmation of CAA and ruling out OSCC in dogs.